INFLUENCE OF WORK-FAMILY CONFLICT AND FAMILY-WORK CONFLICT ON EMPLOYEES’ TURNOVER INTENTIONS WITH GENDER, SOCIAL SUPPORT AND INDIVIDUAL VALUE AS MODERATING EFFECTS - Putu Irma Yunita; Gugup Kismono (Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
work interfering with family-WIF and family interfering with work-FIW) and its influences on turnover intention. This research also examined the moderating effect of gender, social support and individual values on the relationship between the work-family conflict and turnover intentions. The participants of this study were 210 low and middle managers of four and five star hotels in Bali. This sample consisted of 126 males and 84 females. Multiple regression and hierarchical methods were used to test the proposed hypotheses. The result showed that WIF positively and significantly influences the turnover intention but FIW did not. It was also found that social support significantly moderates the relationships between variables studied, but gender and individual value had no impact on it.